Cohesive Devices Usage in Recount Text: An Analysis on High-Achieving Undergraduate EFL Students - Muhammad Firnas Hibatulloh; Koko Lintang Arganata; Irma Khoirot Daulay; Toyyibah Toyyibah (Departement of Mathematics Education, 2024)
Writing is crucial for language proficiency, ensuring clarity and flow through cohesion. This study analyzes the use of cohesive devices in recount texts by high-achieving undergraduate EFL students at a university in Kediri. Using discourse analysis, five student writings were examined to determine the frequency and types of grammatical and lexical cohesive devices. The findings reveal that references and conjunctions are the primary grammatical devices used, with demonstrative references and temporal conjunctions being most prevalent. Lexical cohesion is mainly achieved through repetition, followed by synonyms, meronyms, and hyponyms. While students effectively use these devices to create coherence, there is a heavy reliance on repetition, indicating a need for more variety in lexical strategies. This study highlights the importance of cohesive devices in writing quality and provides insights for educators to develop targeted interventions to enhance students' writing skills.